2011
DOI: 10.1007/s11771-011-0760-0
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive control using interval Type-2 fuzzy logic for uncertain nonlinear systems

Abstract: A new adaptive Type-2 (T2) fuzzy controller was developed and its potential performance advantage over adaptive Type-1 (T1) fuzzy control was also quantified in computer simulation. Base on the Lyapunov method, the adaptive laws with guaranteed system stability and convergence were developed. The controller updates its parameters online using the laws to control a system and tracks its output command trajectory. The simulation study involving the popular inverted pendulum control problem shows theoretically pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…However, the external disturbances are not considered in this research. In [18,19], the interval fuzzy type-II controller is introduced for nonlinear uncertain systems. It is proved that the fuzzy type-II controller handles uncertainties and external disturbances better than the fuzzy type-I controller.…”
Section: Introductionmentioning
confidence: 99%
“…However, the external disturbances are not considered in this research. In [18,19], the interval fuzzy type-II controller is introduced for nonlinear uncertain systems. It is proved that the fuzzy type-II controller handles uncertainties and external disturbances better than the fuzzy type-I controller.…”
Section: Introductionmentioning
confidence: 99%
“…This shows that IT2FLSs have better performance than type-1 fuzzy logic systems (T1FLSs) when confronted with various uncertainties such as dynamic uncertainties, rule uncertainties, external disturbances and noises. See Zhou et al, 36 Ghaemi et al, 37 Wu and Tan 38 and Lin et al 39 . Available information that is used to construct the rules in an FLS can be uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Type‐2 fuzzy sets (T2FSs) as an extension of type‐1 fuzzy sets (T1FSs) were first introduced by Zadeh [10] in 1975. Since then, type‐2 fuzzy logic systems especially interval type‐2 fuzzy logic systems (IT2FLSs) because of their calculation simplicity have been successfully applied to engineering areas, which show IT2FLSs have better performance than type‐1 fuzzy logic systems (T1FLSs) when confronted with various uncertainties like dynamic uncertainties, rule uncertainties, external disturbances and noises, for example, see [11–14]. Hagras and Wagner [15] showed that type‐2 fuzzy logic systems, in contrast to T1FLSs are able to handle higher level of linguistic and numerical uncertainties when applying to real world applications.…”
Section: Introductionmentioning
confidence: 99%